Qualification and certification of Special Patrol Insertion & Extraction (SPIE) equipment for military helicopters - Timmerman, B.; Münninghoff, N. (My University, 2018)
Special Patrol Insertion & Extraction (SPIE) is a type of military operation to rapidly insert personnel in and/or extract personnel from areas where it is not possible to land with a helicopter. The equipment used to perform SPIE operations usually must comply with specifications to ensure adequate performance. Additionally it needs to meet certain airworthiness criteria in order to be certified by the military airworthiness authority. Requirements 27.865 and 29.865 of the civil airworthiness codes provide a useful baseline regarding external loads, which can be adapted to take into account the military operation and environment. This paper discusses the development of the requirements of a qualification and certification programme for a SPIE system to be used on a helicopter. The tests to show compliance with these requirements, both at component level and at system level are discussed as well.